Forms that matter: the Alice B. Toklas Cook Book and the invention of lifestyle writing. Issue 2 (4th May 2022) - Boggs, Colleen Glenney
ABSTRACT: Long neglected in scholarly discussions over critique and new formalism, modernist women's lifestyle writing operates at the fold between realism and modernism, materialism and aesthetics. Poised between high modernism and the cookbooks of the 1930s that fused nineteenth-century home economics with the novel of manners, the Alice B. Toklas Cook Book inaugurated a new form of culinary literature and lifestyle writing, one that was as cultured as it was campy. "Lifestyle" itself emerged as a concept in tandem with modernism, fusing the writerly preoccupation with style (a term neglected in current theoretical discourses that focus on form) to the conduct of life. Alice B. Toklas explored cookbooks for the ways they connected textual and material pleasures, and she drew on dishes, the real ones as well as the realist ones, to reclaim a wholistic understanding of taste.